2015
DOI: 10.1136/annrheumdis-2015-eular.4198
|View full text |Cite
|
Sign up to set email alerts
|

THU0323 The Benefits of 6 Week Home Training Program in Females with Fibromyalgia

Abstract: BackgroundFibromyalgia (FM) is a syndrome expressed by chronic widespread pain which leads to reduced physical function and frequent use of healthcare services (1). The beneficial effects of a relaxation training and aerobic exercise in the management of fibromyalgia (FM) patients were recognized (2).ObjectivesIn our study - a single blind randomized controlled trial – was assessed the effects of a standardized 6 week home training (relaxation training – autotraining Scultz and submaximal aerobic exercise dail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Health professionals included physiotherapists, psychologists, rheumatologists, general practitioners, nurses and social workers. Three abstract-only studies did not explicitly state how the intervention was delivered [41][42][43]. In two studies, group sessions were part of inpatient programmes of one week [44] and four weeks [32].…”
Section: Delivery Modalitymentioning
confidence: 99%
See 3 more Smart Citations
“…Health professionals included physiotherapists, psychologists, rheumatologists, general practitioners, nurses and social workers. Three abstract-only studies did not explicitly state how the intervention was delivered [41][42][43]. In two studies, group sessions were part of inpatient programmes of one week [44] and four weeks [32].…”
Section: Delivery Modalitymentioning
confidence: 99%
“…Ten studies did not provide data sufficient to be included in a meta-analysis: Three studies [47,49,63] reported no significant differences in pain outcome between intervention and control conditions at short-term follow-up. Four studies reported significant reductions in pain severity compared to control groups at short-term follow-up [39,43,59,69]. Amris et al, [31] and Lorig et al, [31,38] measured pain with a focus on long-term outcomes; they…”
Section: Effects Of Multicomponent Self-management Intervention Vs Waitlist/no Treatment/usual Carementioning
confidence: 99%
See 2 more Smart Citations